2004
DOI: 10.4049/jimmunol.173.12.7481
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus-Specific CD8 T Cell Immunity in Old Age: Cytomegalovirus Impairs the Response to a Coresident EBV Infection

Abstract: Aging in humans is associated with increased infections and the reduced proliferative capacity of T cells, part of the more global phenomenon termed immune senescence. The etiology of immune senescence is unknown but the accumulation of virus-specific memory T cells may be a contributory factor. We have examined CD8 T cell responses to two persistent herpesvirus infections, CMV and EBV, and to a recurrent virus infection, influenza, in different age cohorts of healthy donors using HLA-peptide tetramers and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
301
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(324 citation statements)
references
References 43 publications
18
301
4
1
Order By: Relevance
“…The fact that percentages decreased is explained by the increase in total CD8 ϩ T cells after infection with CMV. We thus confirm the finding by others that CMV infection leads to decreased percentages of EBV-specific cells in elderly individuals (19). However, the conclusion cannot be that EBV-specific CD8 ϩ T cells diminished in numbers.…”
Section: Discussionsupporting
confidence: 80%
“…The fact that percentages decreased is explained by the increase in total CD8 ϩ T cells after infection with CMV. We thus confirm the finding by others that CMV infection leads to decreased percentages of EBV-specific cells in elderly individuals (19). However, the conclusion cannot be that EBV-specific CD8 ϩ T cells diminished in numbers.…”
Section: Discussionsupporting
confidence: 80%
“…Experiments in the mouse model of infection with the murine CMV (MCMV) have shown that CMV-specific CD8 T cells accumulate in tissues (3) and in the blood (4) at times when the virus is latent, resulting in an ongoing expansion of CMV-specific T cells called "memory inflation" (4). Similarly, higher frequency of CMV-specific CD8 T cells could be observed with progressing age in blood samples of healthy humans (5), suggesting that HCMV-specific cellular immunity may similarly increase, or "inflate," with age.…”
mentioning
confidence: 89%
“…CMV infection is associated with increased numbers of CD28-or CD45RA+ T-cells in both CD4 and CD8 subsets (Looney et al, 1999) in a manner that recapitulates the aging-related accumulation of these subsets (Chidrawar et al, 2009). CMV is also associated with functional immune deficits in the aging host, including lower counts of Epstein Barr Virus (EBV) specific CD8 T-cells (Khan et al, 2004), increased reactivation of varicella-zoster virus (Ogunjimi et al, 2013) or excess mortality (Roberts et al, 2010;Wikby et al, 2002), mainly due to vascular causes (Roberts et al, 2010;Savva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%